2018
DOI: 10.1111/dmcn.13676
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, course, and outcome of postneonatal presentations of vein of Galen malformation: a large, single‐institution case series

Abstract: Clinical and radiological features in older children with vein of Galen malformation relate to venous hypertension. Outcome is good in most cases with endovascular therapy. Mortality is low but is related to intracranial haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…Compared to a previously reported series from our service, in which 74 per cent of patients had a good outcome but where the neurodevelopmental evaluation was mainly carried out on neonates and infants (81% of the study population), the long‐term evolution described here is much poorer. In a recent review of the literature, Gopalan et al identified good outcome in 65 per cent of patients treated by embolization but did not determine average time of evaluation. A following publication from this group, however, described longer‐term evaluation (median age at testing: 5y 2mo, range: 1–11y) and noted similar results to us: that only half of the surviving patients had a good outcome …”
Section: Discussionmentioning
confidence: 99%
“…Compared to a previously reported series from our service, in which 74 per cent of patients had a good outcome but where the neurodevelopmental evaluation was mainly carried out on neonates and infants (81% of the study population), the long‐term evolution described here is much poorer. In a recent review of the literature, Gopalan et al identified good outcome in 65 per cent of patients treated by embolization but did not determine average time of evaluation. A following publication from this group, however, described longer‐term evaluation (median age at testing: 5y 2mo, range: 1–11y) and noted similar results to us: that only half of the surviving patients had a good outcome …”
Section: Discussionmentioning
confidence: 99%
“…Previously, surgical management of VGAMs was associated with an 80%–100% mortality rate9 and has now been replaced by endovascular treatment 1. Advances in embolisation technology have led to improved patient survival1 10; lower mortality rates in embolised (12%) versus non-embolised (47%) patients have been reported 1. With increasing survival rates, the research focus is shifting to neurological and neurodevelopmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed malformation carries characteristics of both types. Another dilatation of the true vein of Galen seen in cases of hyperdynamic circulation [5-8].…”
Section: Discussionmentioning
confidence: 99%
“…Type IV A is thalamic AVM, type IV B is mesencephalic AVM and type IV C is combined. Type I and II represent the mural type and type III and IV represent the choroidal type [5-8].…”
Section: Discussionmentioning
confidence: 99%